Valuasi Ekonomi Taman Wisata Alam Tawangmangu dengan Menggunakan Metode Biaya Perjalanan - Muntoro, . (Universitas Bangka Belitung, 2010)
This study has three objectives: (1) to know the characteristics of visitors of Tawangmangu Natural Tourism Park, (2) to apply the economic valuation of Tawangmangu Natural Tourism Park by determining the visitorâs willingness to pay, (3) to analyze factors influencing the visitorâs willingness to pay, and factors influencing the visitorâs desirability to revisit the park. The data included the primary data taken by interviewing the visitors from April to June 2009. In order to answer the first objective, an analytical descriptive method was used. The second objective was analyzed by travel cost method. The third objective was analyzed by using double linear regression of the ordinary least squared method and logistic binomial regression analysis. The result suggests (1) the costs of journey significantly influence the amount of the visitors of the park, (2) the total amount of willingnessÂ to pay of the visitors reaches Rp. 287.700.000.000,- in a year. The costs paid by the visitors in a year is Rp. 122.900.000.000,-. Consumerâs surplus of the park in a year isÂ Rp. 164.800.000.000,-. (3) Factors influencing the visitorâs willingness to pay are their monthly income, education level, and their frequency to do field trip in a year, (4) factors influencing the visitorâs desirability to revisit the park are the visitors anxiety level to the tourism places, the accessibility and the satisfaction level to visit the tourism places.Â